PENGARUH PUPUK ORGANIK DAN NITROGEN TERHADAP PERTUMBUHAN DAN HASIL KACANG TANAH (Arachis hypogaea L.) PADA TANAH ULTISOL - Ansi, Azhar (Jurnal Ilmiah Penyuluhan dan Pengembangan Masyarakat, 2023)
The aim of the research was to study the effect of organic fertilizer and Nitrogen (N) on the growth and yield of peanuts on ultisol soils. The study was conducted in the Labibia sub district, Kendari city, from July to October 2023. The study was arranged in a randomized block design (RAK) in a factorial pattern with three replications consisting of 2 factors. The first factor was organic fertilizer which consisted of 4 levels, namely: control (B0), 5 t ha-1 (B1), 10 t ha-1 (B2), and 15 t ha-1 (B3). The second factor was Nitrogen fertilizer which consisted of 3 levels, namely control (P0), 100 kg ha-1 (NPK1), and 200 kg ha-1 (NPK2) so that there were 4x3x3=36 experimental units. Observation variables included: plant height(cm), leaf area(cm2), 100 seed dry weight (g), yield per plot (g) and yield per ha (t ha-1). The results showed that there was an interaction between organic fertilizer and Nitrogen on the observed variables. The best results were obtained on the treatment of 15 t ha-1 of organic fertilizer and 200 kg ha-1 of Nitrogen fertilizer with the highest production reached 2.21 t ha-1.